The Spatial Dimension of Interreligious Dialogue: The Case of an Orthodox Church in Turin - Caterina Pignotti; Maria Chiara Giorda (Religions)
Urban space is the social field in which religious diversity in contemporary Italy becomes most evident and where religious groups compete for visibility, recognition, and places of worship. The sites of so-called minorities can be observed as indicators of a plural religious geography. Peaceful and conflictual dynamics are both expressed precisely through external recognition, which may be horizontal—religious and social—when between peers or vertical therefore juridical. This study presents the findings of research conducted in the city of Turin, an emblematic case within the Italian religious landscape for the management of religious diversity and interreligious dialogue initiatives. The analysis focuses on the Romanian Orthodox Church located in the historic center, which we interpret as a shared religious place. This case shows how a spatial and material perspective can offer an innovative approach to the field of interreligious dialogue. Places of worship are crucial spaces for interreligious dialogue: they serve as laboratories of local peace-building and experiments in coexistence, mutual respect, encounter, and conflict mediation. However, in a frame of multiple secularities, the ambiguity of both the national and regional legal systems contribute to marginality of the religious dimension in the city’s urban planning policies, ignoring the important role these places play as spaces of cohesion, identity, inclusion.